2008
DOI: 10.1002/0471250953.bi0712s22
|View full text |Cite
|
Sign up to set email alerts
|

Using GenePattern for Gene Expression Analysis

Abstract: The abundance of genomic data now available in biomedical research has stimulated the development of sophisticated statistical methods for interpreting the data, and of special visualization tools for displaying the results in a concise and meaningful manner. However, biologists often find these methods and tools difficult to understand and use correctly. GenePattern is a freely available software package that addresses this issue by providing more than 100 analysis and visualization tools for genomic research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 17 publications
1
82
0
Order By: Relevance
“…The reciprocal analysis in which we gated first on splenic virus-specific CD4 T cells that express EOMES showed that these cells expressed equivalent amounts of PD1 ( Figure 2E), but TGFβ-RII-deficient EOMES + cells were enriched for Ly6C + PSGL1 + cells ( Figure 2F). In addition, IFN-γ-producing Th1 CD4 T cells after GP [67][68][69][70][71][72][73][74][75][76][77] peptide stimulation (from Figure 1F) expressed more granzyme B in the spleen and lung (Figure 2G). Collectively, these results demonstrate that in the absence of TGF-β signaling, virus-specific CD4 T cells showed enhanced terminal differentiation and increased expression of cytotoxic molecules.…”
Section: Smad4 and Eomes Exerted Opposing Roles In Accumulation And Dmentioning
confidence: 99%
See 2 more Smart Citations
“…The reciprocal analysis in which we gated first on splenic virus-specific CD4 T cells that express EOMES showed that these cells expressed equivalent amounts of PD1 ( Figure 2E), but TGFβ-RII-deficient EOMES + cells were enriched for Ly6C + PSGL1 + cells ( Figure 2F). In addition, IFN-γ-producing Th1 CD4 T cells after GP [67][68][69][70][71][72][73][74][75][76][77] peptide stimulation (from Figure 1F) expressed more granzyme B in the spleen and lung (Figure 2G). Collectively, these results demonstrate that in the absence of TGF-β signaling, virus-specific CD4 T cells showed enhanced terminal differentiation and increased expression of cytotoxic molecules.…”
Section: Smad4 and Eomes Exerted Opposing Roles In Accumulation And Dmentioning
confidence: 99%
“…Cytokine measurements. Secretion of IFN-γ, TNF-α, and IL-2 from LCMV-specific T cells was performed ex vivo using GP [31][32][33][34][35][36][37][38][39][40][41] or GP [67][68][69][70][71][72][73][74][75][76][77] peptide stimulation of splenocytes incubated in the presence of 1 μg/ ml brefeldin A (BFA; Sigma-Aldrich) for 5 hours at 37˚C before staining.…”
Section: Cd49dmentioning
confidence: 99%
See 1 more Smart Citation
“…-F ullOne and F ullM any are the two strategies to encode full lineage, and P ayOne and P ayM any encode payload lineage 4 . Figure 4 depicts how the backward-optimied implementation of these strategies encode two output cells with coordinates (0, 1) and (2, 3) that depend on input cells with coordinates (4, 5) and (6, 7).…”
Section: B Encodermentioning
confidence: 99%
“…Prior work in data lineage tracking systems has largely been limited to coarse-grained metadata tracking [3], [4], which stores relationships at the file or relational table level. Finegrained lineage tracks relationships at the array cell or tuple level.…”
Section: Introductionmentioning
confidence: 99%